Grumpy, a relatively new marketing agency in the industry, determining their core services, addressing overstretched human resources and being prepared for the ever-changing volatile environment of the specific industry - Rafsun, Muhtasim Fuad (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.